A beginners guide to Mathematica - McMahon, David; Topa, Daniel M (Chapman & Hall/CRC, 2006)
Although powerful and very popular in science and engineering, Mathematica can be difficult to learn because of its large command structure and intricate syntax. This book offers a simple, step-by-step approach to help newcomers to Mathematica build the skills needed to use the software in practice.